DISTRIBUSI FREKUENSI KEHILANGAN GIGI BERDASARKAN KLASIFIKASI KENNEDY DITINJAU DARI TINGKAT PENDAPATAN MASYARAKAT KELURAHAN PEUNITI BANDA ACEH - Liana Rahmayani; Poppy Andriany (Faculty of Dentistry, Universitas Islam Sultan Agung, 2015)
Background: The missing teeth are substantially can influence the whole of general and oral health quality. That also can be the oral health indicator in a population. Partial edentulous teeth is a missing condition of one or several teeth that can cause the loosing of function which causing by a disease or specific condition. Kennedy classification is to classify the state division of some missing teeth include bilateral posterior Kennedy class I edentulous area (free end), Kennedy class II posterior unilateral edentulous area, Kennedy class III unilateral or bilateral edentulous (bounded), class IV Kennedy Single Edentulous Area used as the reference of anterior to see partial missing teeth area. Purpose: The study aims to see the frequency distribution of partial edentulous based on the Kennedy classification with income levels at the Peuniti Village society in Banda Aceh aged 35-44 years. Method: The study began the selection of the subject at the Peuniti Village in Banda Aceh with missing teeth oral examination and fill the questionaire. The study was using univariate analysis to see the frequency distribution of missing teeth in subject at Peuniti Village Banda Aceh. Result: The result showed that partial edentulous based on the Kennedy classification with income level at Peuniti Village society inBanda Aceh was higher in class III and found at age 35-44 years.